Extractability of heavy metals in saline and non-saline soils treated with municipal wastewater under two contrasting moisture regimes - M. Safari Sinegani; A.A. Safari Sinegani; M. Hadipour (Environmental Resources Research, 2018)
Solubility and bioavailability of heavy metals are important with respect to theirtoxicity. The discharge of municipal wastewater in soil and surface waters can affectbioavailability and mobility of heavy metals in soils and sediments. The effect of dischargeof Arak municipal wastewater on the KNO3 and DTPA extractable heavy metals in a salinesoil sampled from Mighan playa (Iran) compared to a non-saline agricultural soil wasstudied in two moisture regimes (field capacity and flooding) in three incubation times (1,150 and 365 day). In the saline soil, the addition of wastewater led to increase of organiccarbon (OC) and decrease of Eh, pH and EC. However, in the non-saline soil, the additionof wastewater led to increase of EC and decrease of TOC and Eh simultaneously. With veryfew exceptions, the addition of wastewater increased the KNO3 and DTPA extractableheavy metals significantly. These changes were higher in the saline submerged soil. So, theaddition of municipal wastewater in soils for irrigation of saline and non-saline croplandswas safer than when it was applied in waterlogged soils. The changes of the analyzedproperties were higher in the saline soil compared to those in the non-saline soil. Hence, theresilience of the saline soil compared to the non-saline soil due to its lower bufferingcapacity was considerably lower. We can conclude that the release of wastewater toMighan playa soil with high level of salinity may increase the bioavailability and mobilityof heavy metals towards that lake.